Spiritual Revolution: the Story of Operation Mobilization OM - Randall I.; Randall Ian (Milton Keynes Colorado Springs Hyderabad Authentic, 2008)
Spiritual Revolution tells the story of 50 years of Operation Mobilization (OM). Beginning with an account of George Verwers conversion and OMs early outreach in Mexico, Gods faithfulness is seen as OM has grown to include today more than 4,000 workers serving in over 100 countries. A highly-readable account of OMs history attractive to all Christians interested in mission, Spiritual Revolution is more than just a story. Author Ian Randall presents us with significant insights which will be of importance to serious students of mission. The spirituality underlying the organization, the pioneering of short-term mission, and the catalytic impact of OM in East Asia, Latin America, southern Africa, and beyond are among the important missiological themes covered in this ground-breaking history. Also included is an 8 page illustrated pictoral history with black and white and color photographs.
Keywords: 27 (NhRISTIQNSTWOs